A programmable testbed for spectrum survey in the Philippines-measurements and analyses - Pintor, Annie Liza (Philippine Engineering Journal [eJournal])
This study investigates white spaces in the frequency range 410 MHz to 960 MHz using a programmable measurement testbed. Radio spectrum scanning was performed for a total of 144 hours (6 days at 24 hours/day) with the main objective of identifying and quantifying the white space contained in the said bandwidth as a preliminary phase in developing a repository for spectrum utilization in future work. Channel occupancy based on NTC's 2016 channel plan was evaluated herewith. Results show underutilization of the observed bandwidth, with highest average channel occupancy to be 45.12% which is utilized by Cellular Mobile Telephone System in the frequent band, 925 to 960 MHz. Occupancy results show that the observed frequency band contains a large amount of white space. This could be used for different applications, whether for connectivity improvement, government's social services or simply public awareness of the spectrum utilization. This study serves as a foundation for future studies that may include a real-time spectrum observatory and similar applications.